Thiophene- and carbazole-substituted N-Methyl-Fulleropyrrolidine acceptors in PffBT4T-2OD based solar cells - Gaspar, Hugo (2020)
The impact of fullerene side chain functionalization with thiophene and carbazole groups on the device properties of bulk-heterojunction polymer:fullerene solar cells is discussed through a systematic investigation of material blends consisting of the conjugated polymer poly[(5,6-difluoro-2,1,3-benzothiadiazol-4,7-diyl)-alt-(3,3‴-di(2-octyldodecyl)-2,2′;5′,2″;5″,2‴-quaterthiophen-5,5‴-diyl)] (PffBT4T-2OD) as donor and C60 or C70 fulleropyrrolidines as acceptors. The photovoltaic performance clearly depended on the molecular structure of the fulleropyrrolidine substituents although no direct correlation with the surface morphology of the photoactive layer, as determined by atomic force microscopy, could be established. Although some fulleropyrrolidines possess favorable lowest unoccupied molecular orbital levels, when compared to the standard PC71BM, they originated OPV cells with inferior efficiencies than PC71BM-based reference cells. Fulleropyrrolidines based on C60 produced, in general, better devices than those based on C70, and we attribute this observation to the detrimental effect of the structural and energetic disorder that is present in the regioisomer mixtures of C70-based fullerenes, but absent in the C60-based fullerenes. These results provide new additional knowledge on the effect of the fullerene functionalization on the efficiency of organic solar cells.